SISI LAIN DARI MAKNA ASET EKONOMI - Irma Mamulati (Universitas Muhammadiyah Malang, 2017)
This study aims to reveal the other side of the meaning economic assets in Amal UsahaMuhammadiyah. This research uses qualitative paradigm with phenomenology interpretivemethods to interpret the other side of the meani ng economic assets in Amal UsahaMuhammadiyah as a research site. The result exposes other side of the meaning economicassets: first, the assets as a means of dakwah. Second, assets as a means of correlate fraternity.Third, the assets as a means of organizational sustainablility.Kata Kunci: Aset Ekonomi, Sarana Dakwah, Bersilarurahmi, Keberlanjutan Organisasi, AmalUsaha Muhammadiyah, Fenomenologi